Improving soil fertility with lime and phosphogypsum enhances soybean yield and physiological characteristics - Bossolani, João William [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Moretti, Luiz Gustavo [UNESP]; Garcia, Ariani [UNESP]; Portugal, José Roberto [UNESP]; Bernart, Leila [UNESP]; Vilela, Rafael Gonçalves [UNESP]; Caires, Eduardo Fávero; Amado, Telmo Jorge Carneiro; Calonego, Juliano Carlos [UNESP]; dos Reis, André Rodrigues [UNESP] (Springer Nature, 2022)
In tropical no-till systems, applying lime (L) and phosphogypsum (PG) on the soil surface may be a potential strategy for reducing soil acidification and improving soybean root growth, thereby enhancing plant nutrition and physiological responses and, in turn, crop resistance to dry spells. This study evaluated the impact of long-term (17 years) surface soil amendment on soil fertility and soybean root development, nutrition, gas exchange, carbon and antioxidant enzyme activity, and grain yield in a tropical region subject to dry spells. The treatments consisted of the following long-term soil amendments: control (no soil amendment); L alone; PG alone; and L + PG (LPG). Liming, especially when combined with PG, improved soil fertility, as evidenced by increases in pH and P, Ca2+, and Mg2+ levels throughout the soil profile, but reduced Al3+ and micronutrients (Fe, Mn, Cu, and Zn). The improvements in soil fertility were associated with increased root development throughout the profile. Long-term application of LPG reduced the negative impacts of dry spells on pigment concentrations, gas exchange, Rubisco and sucrose synthase activities and antioxidant metabolism, and increased soybean grain yield. Our results reveal that long-term application of LPG is an important approach for increasing the vertical movement of cationic bases and roots in no-till systems to improve soybean nutrition. Long-term amendment with LPG enhanced both carbon and antioxidant metabolism in soybean plants, resulting in higher soybean grain yield, despite the predisposition of this tropical region to dry spells.
Keywords: Glycine max (L.) Merrill; Oxidative stress; Rubisco; Soil acidity; Soil amendments; Sucrose synthase